Blood Lead Testing in Flint Before and After Water Contamination - Jenkins, Derek; Grossman, Daniel; Slusky, David; Danagoulian, Shooshan (Pediatrics (Evanston), 2022)
Lead is a neurotoxicant that negatively affects health. Reducing lead exposure and early detection among children are important public health goals. Our objective with this study was to determine if the September 2015 lead advisory in Flint, Michigan affected lead testing among children when possible exposure was widely publicized. This study included 206 001 children born in Michigan from 2013 to 2015 and enrolled in Medicaid, using 2013 to 2017 claims data to determine if and at what age an individual received a lead test. Difference-in-differences regression models were used to compare the receipt of lead tests among children in Flint with other cities in Michigan before and after September 2015, when a lead advisory was issued for the city warning about potential exposure to lead in publicly supplied water. Before the lead advisory, approximately 50% of children in Flint received a lead test by 12 months of age and nearly 75% received a lead test by 24 months of age. After the September 2015 advisory, the receipt of lead tests among children in Flint increased 10 percentage points by 12 months compared with other cities. Effects by 10-month cohorts, as of 2016, revealed a 20-percentage-point increase for children in Flint compared with other cities. Despite a highly publicized lead advisory, children in Flint enrolled in Medicaid received lead tests earlier, but the proportion of Medicaid-eligible children who were tested did not change. This suggests that increasing lead testing is a difficult policy goal to achieve and, therefore, supports recent efforts focusing on primary prevention to reduce lead exposure.